Basics of analytical chemistry and chemical equilibria - Tissue, Brian M., 1961- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
BEnables students to progressively build and apply new skills and knowledge/b/ Designed to be completed in one semester, this text enables students to fully grasp and apply the core concepts of analytical chemistry and aqueous chemical equilibria. Moreover, the text enables readers to master common instrumental methods to perform a broad range of quantitative analyses. Author Brian Tissue has written and structured the text so that readers progressively build their knowledge, beginning with the most fundamental concepts and then continually applying these concepts as they advance to more sophisticated theories and applications. iBasics of Analytical Chemistry and Chemical Equilibria /iis clearly written and easy to follow, with plenty of examples to help readers better understand both concepts and applications. In addition, there are several pedagogical features that enhance the learning experience, including:ulliEmphasis on correct IUPAC terminology/lili"You, Try, It" spreadsheets throughout the text, challenging readers to apply their newfound knowledge and skills/liliOnline tutorials to build readers' skills and assist them in working with the text's spreadsheets/liliLinks to analytical methods and instrument suppliers/liliFigures illustrating principles of analytical chemistry and chemical equilibria/liliEnd, of, chapter exercises/li/ul iBasics of Analytical Chemistry and Chemical Equilibria/i is written for undergraduate students who have completed a basic course in general chemistry. In addition to chemistry students, this text provides an essential foundation in analytical chemistry needed by students and practitioners in biochemistry, environmental science, chemical engineering, materials science, nutrition, agriculture, and the life sciences.
Chapter 9: Atomic Spectrometry9.1 Atomization; 9.2 Atomic Absorption Spectrometry (AAS); 9.3 Atomic Emission Spectrometry (AES); 9.4 Introduction to Mass Spectrometry (MS); 9.5 ICP-MS Measurements; 9.6 Summary; Practice Exercises; Chapter 10: Analytical Separations; 10.1 Thin-Layer Chromatography; 10.2 Chromatogram Terminology; 10.3 Column Selection; 10.4 High Performance Liquid Chromatography; 10.5 Gas Chromatography; 10.6 Molecular Mass Spectrometry; 10.7 ELECTROPHORESIS; Practice Exercises; Index.
"Published simultaneously in Canada"--Title page verso.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Chemistry, Analytic -- Textbooks; Chemical equilibrium -- Textbooks; Chemical equilibrium -- Textbooks; Chemical equilibrium; Chemistry, Analytic -- Textbooks; Chemistry, Analytic; SCIENCE -- Chemistry -- Analytic; Chemical equilibrium; Chemistry, Analytic; Electronic books; Textbooks; Electronic books